(untitled) (Journal of Organizational Psychology, 2021)
We highlight the importance of individual work identity as organizational identification’s counterpart in the new world of work and propose a theoretical model regarding the influences of affective events and worker agency on gig worker identity construction. We suggest individual work identity perceptions can be generated by negotiated exchanges with organizations, groups, and networks that may serve as organizational proxies. Drawing on Affective Events Theory and Sense of Agency, we assert that the physical, temporal, and administrative connections with an organization interact with work configuration to influence the affective reactions that impact individual work identities in the gig economy context.